Hospital admission for acute pancreatitis in an English population, 1963-98: database study of incidence and mortality. - Goldacre, M; Roberts, SE (2004)
OBJECTIVES: To investigate trends in the incidence of acute pancreatitis resulting in admission to hospital, and mortality after admission, from 1963 to 1998. DESIGN: Analysis of hospital inpatient statistics for acute pancreatitis, linked to data from death certificates. SETTING: Southern England. SUBJECTS: 5312 people admitted to hospital with acute pancreatitis. MAIN OUTCOME MEASURES: Incidence rates for admission to hospital, case fatality rates at 0-29 and 30-364 days after admission, and standardised mortality ratios at monthly intervals up to one year after admission. RESULTS: The incidence of acute pancreatitis with admission to hospital increased from 1963-98: age standardised incidence rates were 4.9 per 100,000 population in 1963-74, 7.7 in 1975-86, and 9.8 in 1987-98. Age standardised case fatality rates within 30 days of admission were 14.2% in 1963-74, 7.6% in 1975-86, and 6.7% in 1987-98. From 1975-98, standardised mortality ratios at 30 days were 30 in men and 31 in women (compared with the general population of equivalent age in the same period = 1), and they remained significantly increased until month 5 for men and month 6 for women. CONCLUSIONS: Incidence rates for acute pancreatitis with admission to hospital rose in both men and women from 1963 to 1998, particularly among younger age groups. This probably reflects, at least in part, an increase in alcoholic pancreatitis. Mortality after admission has not declined since the 1970s. This presumably reflects the fact that no major innovations in the treatment of acute pancreatitis have been introduced. Pancreatitis remains a disease with a poor prognosis during the acute phase.